2011
DOI: 10.1007/s11244-011-9673-2
|View full text |Cite
|
Sign up to set email alerts
|

Gold Stabilized by Nanostructured Ceria Supports: Nature of the Active Sites and Catalytic Performance

Abstract: The interaction of gold atoms with CeO 2 nanocrystals having rod and cube shapes has been examined by cyanide leaching, TEM, TPR, CO IR and X-ray absorption spectroscopy. After deposition-precipitation and calcination of gold, these surfaces contain gold nanoparticles in the range 2-6 nm. For the ceria nanorods, a substantial amount of gold is present as cations that replace Ce ions in the surface as follows from their first and second coordination shells of oxygen and cerium by EXAFS analysis. These cations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 81 publications
9
81
0
Order By: Relevance
“…In previous work with Au catalysts, the authors had to leach out the metallic component before performing catalytic tests 2,20 . Even if the initial catalyst is in the form of atomically dispersed species, the catalyst can evolve during reaction measurement, as shown by Guan et al 21 and, more recently, by Corma et al 22 These authors suggest that atomically dispersed species can serve as precursors for the formation of very small clusters of the metal. Hence, it is necessary to use in situ spectroscopy to confirm the identity of the species responsible for catalytic reactivity.…”
Section: Resultsmentioning
confidence: 98%
“…In previous work with Au catalysts, the authors had to leach out the metallic component before performing catalytic tests 2,20 . Even if the initial catalyst is in the form of atomically dispersed species, the catalyst can evolve during reaction measurement, as shown by Guan et al 21 and, more recently, by Corma et al 22 These authors suggest that atomically dispersed species can serve as precursors for the formation of very small clusters of the metal. Hence, it is necessary to use in situ spectroscopy to confirm the identity of the species responsible for catalytic reactivity.…”
Section: Resultsmentioning
confidence: 98%
“…The calculation performed for the ceria of low LSA area shows that N L is the same (N L =0. 15) and therefore that the OSC process is only dependent on the surface area for a given oxide. In contrast to what was expected, the N L values were higher when ceria was supported on alumina.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of Electronic supplementary material The online version of this article (doi:10.1007/s13404-013-0103-z) contains supplementary material, which is available to authorized users. the ceria crystallites, the size of the gold clusters (particles), and the oxidation state of the active gold atoms are the parameters usually discussed because of their determining importance for the catalytic oxidation activity [15]. The nature of the intermediate species is also studied.…”
Section: Introductionmentioning
confidence: 99%
“…70 The activities in WGSR followed the sequence of Au/CeO 2 nanorods > Au/CeO 2 polyhedra c Au/ CeO 2 nanocubes, probably because of the presence of a much higher fraction of strongly bound gold species on the former two catalysts, as confirmed by others. 81 In addition, a theoretical study indicated that oxygen vacancies are easier to form on CeO 2 {110} than {100} and {111} planes, 82 thus explaining the stabilization of gold species on CeO 2 nanorods. A similar effect was established for the methanol steam reforming on Au/CeO 2 catalysts, 83 and the shape effects on metal oxide supported gold catalysts in WGSR were reported in Au/ZnO and Au/Fe 3 O 4 systems.…”
Section: Development Of New Wgs Catalystsmentioning
confidence: 99%
“…137 Hensen and co-workers showed that the cationic gold in leached Au/CeO 2 could be partially reduced to metallic gold clusters active for hydrogenation of 1,3-butadiene, CO oxidation, and WGSR. 81,138 Rodriguez and co-workers studied Au/Ce(Gd)O 2 and Au/ CeO x /TiO 2 using in situ time-resolved X-ray absorption spectroscopy (TR-XAS). 114,140 They also found the transformation of cationic gold into metallic gold under WGS conditions.…”
Section: Nature Of Active Sitesmentioning
confidence: 99%